Platinum Nanoparticles Suppress Osteoclastogenesis Through Scavenging of Reactive Oxygen Species Produced in RAW264.7 Cells - Mayumi Nomura; Yoshitaka Yoshimura; Takashi Kikuiri; Tomokazu Hasegawa; Yumi Taniguchi; Yoshiaki Deyama; Ken-ichi Koshiro; Hidehiko Sano; Kuniaki Suzuki; Nobuo Inoue (Elsevier, 2011)
Abstract.: Recent research has shown that platinum nanoparticles (nano-Pt) efficiently quench reactive oxygen species (ROS) as a reducing catalyst. ROS have been suggested to regulate receptor activator of NF-κB ligand (RANKL)-stimulated osteoclast differentiation. In the present study, we examined the direct effects of platinum nano-Pt on RANKL-induced osteoclast differentiation of murine pre-osteoclastic RAW 264.7 cells. The effect of the nano-Pt on the number of osteoclasts was measured and their effect on the mRNA expression for osteoclast differentiation was assayed using real-time PCR. Nano-Pt appeared to have a ROS-scavenging activity. Nano-Pt decreased the number of osteoclasts (2+ nuclei) and large osteoclasts (8+ nuclei) in a dose-dependent manner without affecting cell viability. In addition, this agent significantly blocked RANKL-induced mRNA expression of osteoclastic differentiation genes such as c-fms, NFATc1, NFATc2, and DC-STAMP as well as that of osteoclast-specific marker genes including MMP-9, Cath-K, CLC7, ATP6i, CTR, and TRAP. Although nano-Pt attenuated expression of the ROS-producing NOX-family oxidases, Nox1 and Nox4, they up-regulated expression of Nox2, the major Nox enzyme in macrophages. These findings suggest that the nano-Pt inhibit RANKL-stimulated osteoclast differentiation via their ROS scavenging property. The use of nano-Pt as scavengers of ROS that is generated by RANKL may be a novel and innovative therapy for bone diseases. Keywords:: platinum nanoparticle, osteoclast, reactive oxygen species (ROS), NOX, RAW cell